IMPLEMENTASI PEMBELAJARAN TEMATIK KURIKULUM 2013 PADA PENDIDIKAN ANAK USIA DINI - Raisah Armayanti Nasution (Universitas Islam Negeri Sumatera Utara, 2018)
Thematic learning of early childhood education is conducted in an integrated and comprehensive manner for every field of development. This is in accordance with the child's thinking characteristics that are still holistic. children still see things as a whole, not fragmented and not yet focused on certain elements.Thematic teaching of early childhood in the 2013 curriculum using the Spiderwebbed Model (spiderwebbed). in this lesson is based on the selection of themes and sub-themes with due regard to the relationship with child development. Keyword: early childhood, education, Thematic learning